Metal-Free 2D/2D van der Waals Heterojunction Based on Covalent Organic Frameworks for Highly Efficient Solar Energy Catalysis - Yan, Ge; Sun, Xiaodong; Zhang, Yu; Li, Hui; Huang, Hongwei; Jia, Baohua; Su, Dawei; Ma, Tianyi (Nano-Micro Letters, 2023)
Covalent organic frameworks (COFs) have emerged as a kind of rising star materials in photocatalysis. However, their photocatalytic activities are restricted by the high photogenerated electron–hole pairs recombination rate. Herein, a novel metal-free 2D/2D van der Waals heterojunction, composed of a two-dimensional (2D) COF with ketoenamine linkage (TpPa-1-COF) and 2D defective hexagonal boron nitride (h-BN), is successfully constructed through in situ solvothermal method. Benefitting from the presence of VDW heterojunction, larger contact area and intimate electronic coupling can be formed between the interface of TpPa-1-COF and defective h-BN, which make contributions to promoting charge carriers separation. The introduced defects can also endow the h-BN with porous structure, thus providing more reactive sites. Moreover, the TpPa-1-COF will undergo a structural transformation after being integrated with defective h-BN, which can enlarge the gap between the conduction band position of the h-BN and TpPa-1-COF, and suppress electron backflow, corroborated by experimental and density functional theory calculations results. Accordingly, the resulting porous h-BN/TpPa-1-COF metal-free VDW heterojunction displays outstanding solar energy catalytic activity for water splitting without co-catalysts, and the H2 evolution rate can reach up to 3.15 mmol g−1 h−1, which is about 67 times greater than that of pristine TpPa-1-COF, also surpassing that of state-of-the-art metal-free-based photocatalysts reported to date. In particular, it is the first work for constructing COFs-based heterojunctions with the help of h-BN, which may provide new avenue for designing highly efficient metal-free-based photocatalysts for H2 evolution. Highlights: 1 It is the first attempt to combine covalent organic frameworks with hexagonal boron nitride (h-BN) to construct efficient metal-free photocatalyst. 2 The composite displays superior photocatalytic hydrogen production performance in metal-free systems. 3 The integrated porous h-BN can suppress electron backflow to optimize the composite photocatalytic activity.